Biomechanical analysis of low back pain in breaststroke swimmers - Colman, V.; Persyn, U.; Winters, W. (International SportMed Journal, 2000)
Health professionals, including physical education (PE) teachers and physiotherapists, can be trained to conduct biomechanical assessments of average swimmers in order to correct techniques and prevent injuries. Specific causes of low back pain in breaststroke swimmers can be detected based on a movement analysis of PE students experiencing pain in this stroke. Their faulty techniques were analyzed as case studies to generate an interactive computer-aided instruction (CAI) program that makes extensive use of animations. In this review, the specific causes of low back pain in breaststroke swimmers are described from the points of view of poor balance mechanics and body hyperextension, measured with a special video-digitizing system. As an introduction to the CAI program, this review could improve the biomechanical diagnosis of health professionals.